Genomic Instability and Cellular Senescence: Lessons From the Budding Yeast - Lee, Jee Whu; Ong, Eugene Boon Beng (Frontiers in Cell and Developmental Biology, 2021)
Ageing is a complex biological process that occurs in all living organisms. Ageing is initiated by the gradual accumulation of biomolecular damage in cells leading to the loss of cellular function and ultimately death. Cellular senescence is one such pathway that leads to ageing. The accumulation of nucleic acid damage and genetic alterations that activate permanent cell-cycle arrest triggers the process of senescence. Cellular senescence can result from telomere erosion and ribosomal DNA instability. In this review, we summarise the molecular mechanisms of telomere length homeostasis and ribosomal DNA stability, and describe how these mechanisms are linked to cellular senescence and longevity through lessons learned from budding yeast.